Development of an ion transport system for singly charged ion injection into an electron string ion source (ESIS) charge-breeder - Segal, Matthew (Department of Physics, 2021)
A 1+ ion delivery system was designed and constructed for the purpose of ion injection into the Electron String Ion Source (ESIS) charge-breeder at the Joint Institute for Nuclear Research (JINR) in Dubna, Russia. The transport system was initially developed at iThemba LABS in Cape Town. This system includes a Liquid Metal Ion Source (LMIS) and an ion extraction and focusing system. The ion delivery system is used to produce Ga+ and Au+ ions which are transported through a beam-line system consisting of charged particle optics such as focusing einzel-lenses, an electrical quadrupole switchyard for 90◦ beam bending, and subsequent correction and focusing lenses before the entry port into the ESIS. A replica of the full system was created and used to study injection and ion transport efficiency before implementation with the ESIS. A multi-wire harp beam profilometer was used to study ion beam profiles and to obtain geometric parameters of Ga+ beams. Ga+ injection into the KRION 6T ESIS was performed successfully using the ion injection system. The extraction of multiply charged gallium was successful after 1+ injection into the KRION 6T ESIS, with a maximum charge-state of 23+. Although 1+ to n+ injection has been performed with similar Electron Beam Ion Source (EBIS) devices, this work is the first case of 1+ to n+ injection using the ESIS. This research was conducted within the frame-work of the South Africa/JINR collaboration and has been funded by the National Research Foundation (NRF).